Influence of experimental Anaplasma marginale infection and splenectomy on NTPDase and 5'nucleotidase activities in platelets of cattle. (June 2016) - Doyle, Rovaina L.; Oliveira, Camila B.; França, Raqueli T.; Doleski, Pedro H.; Souza, Viviane C.; Leal, Daniela B.R.; Martins, João R.; Lopes, Sonia T.A.; Machado, Gustavo; Da Silva, Aleksandro S.; Andrade, Cinthia M.
Abstract: The objective of this paper was to evaluate NTPDase and 5'-nucleotidase activities in platelets of bovine with and without spleen and infected by Anaplasma marginale . Our results demonstrate that infection along with splenectomy is able of inducing a profile of cellular protection, which showed an increase in the degradation of the nucleotides ATP and ADP by NTPDase, in addition to AMP by 5'nucleotidase to form the nucleoside adenosine in platelets, i.e., the enzymatic activities of platelets were increased in splenectomized animals when compared to non-splenectomized group. It notes that adenosine is a molecule with anti-inflammatory function. But this profile is related to a deficiency in immune signaling triggered by nucleotide ATP, which may be related to the increase in bacteremia and disability in combating the parasite in splenectomized host. Highlights: Anaplasma marginale is a pathogen that infected cattle and has worldwide distribution. The NTPDase and 5'-nucleotidase in platelet modulates physiological functions aimed at protecting the body in general. Infection by A . marginale is capable of producing cell and tissue damage. Changes occurs in NTPDase and 5'-nucleotidase activities in A. marginale infection of cattle. Removal of the spleen in infected animals influences the activity of the enzymes of the purinergic system.